BESKALAN LANANG DANCE MODIFICATION AS A INSTRUMENT OF SUPPLYING OF MARKET NEEDS - Desy Lusiana; Eko Sasmito (Journal of Aesthetics, Design, and Art Management, 2021)
Purpose: This article describes the phenomenon of the practice of modifying the Beskalan Lanangdance. Beskalan Lanang dance is a traditional dance from Malang Regency which existed in 2000and is currently experiencing a significant decline. Beskalan Lanang dance depicts a brave andstrong warrior in the middle of his life without his parents. This article is very relevant to the field ofcultural studies because it examines the relationship between the Beskalan Lanang dance, Tourism,and Capitalism.Research methods: This article uses literature and interview methods. The article data ispresented in a qualitative descriptive form and the data analysis uses Bourdieu's Theory of Practice.Findings: The various movements presented in the Beskalan Lanang dance are very thick with thevalues of the nation's character such as tolerance, communication, creativity, independence, peace-loving, and social care. All of these values seem to have been neglected when the Beskalan Lanangdance is faced with tourism needs. To supply the market demand, the Beskalan Lanang dance hasbeen repackaged in such a way, which was originally presented with a duration of 20 minutes buthas been changed to 11 minutes. Because of this, the Beskalan lanang dance will change its formand presentation structure, so that many values are neglected.Implications: The practice of modifying the Beskalan Lanang dance is carried out by actors whohave fund and fund has been converted to legitimize the practice of modifying the Beskalan Lanangdance, so it is very clear that the element of capitalism is closely attached to the rework of theBeskalan Lanang dance.